Pinioing in Iraq Swan - Shanian, H.; Ali, H.; Mahmood, T. K. (The Iraqi Journal of Veterinary Medicine, 1999)
Have been done on 30 swan by two methods tenotomy for the extensor tendon of the distal articulation of the left wing and by amputation of the distal articulation of the left wing all operation done under local anaesthesia no any complication have been seen and tenotomy technique is more suitable for this kind of birds because bird will have its normal shape.